Discrimination in speech: Categorization of women under the focus of systemic-functional grammar - Santos, Claudia Moreira dos; Ikeda, Sumiko Nishitani (The ESPecialist, 2014)
The objective of this study is to compare the categorization of women and men on the first page of Folha de S. Paulo newspaper, under the light of Critical Linguistics, with the support of Systemic Functional Grammar (SFG). For this purpose, the study shall answer the following questions: (a) How often are women or men cited on the first page of Folha de S. Paulo newspaper? (b) What type of activities are women and men cited on these pages engaged in? (c) Which lexico-grammatical choices does the ideology behind the image of woman and man reveal?